ARE THE ANTIBIOTICS ALWAYS NECESSARY FOR THE TREATMENT OF THE CHRONIC COUGH AMONG CHILDREN? - L.L. Nisevich; L.S. Namazova; K.S. Volkov; I.M. Vazhnova; V.V. Botvin'eva; I.V. Zubkova; E.G. Filyanskaya (Union of pediatricians of Russia, 2008)
Cough is one of the main symptoms for the impairment of the respiratory passages. Nonetheless, cough may usually appear along with the development of a pathological process in other organs and systems. Authors point to the importance of its correct estimate for the differential diagnosis. They have examined the reasons for the cough among children, depending on the age of a child, related symptoms, duration and other properties of the cough itself. They studied etiological structure of diseases, in the course of which such a symptom comes to existence. They also analyzed the detection rate of the viral and intracellular causative agents in the aspirates among chronically coughing children, as well as the indicators of the humoral immunity to the intracellular causative agents. Besides, the article deals with the questions of the adequate antibechic therapy.Key words: cough, etiology, pathogenesis, differential diagnosis, viruses, intracellular causative agents, treatment, children.